Joining Enterprises with Web 2.0 big push in 2006. - Linthicum, David
The notion of building bridges to service providers and managing the interaction will become more commonplace in 2006 as we learn to accept that many services we leverage within an enterprise are services we may not host. The technology exists today. We need to define and refine our approaches now, including architectures, enabling technology and use of standards. Most enterprises are way behind.